The Emergence of Low Carbon Energy Autonomy in Isolated Communities - Rae, Callum; Bradley, Fiona (Journal of Technology Innovations in Renewable Energy, 2013)
This study examines the concept of switching from a centralised energy supply model towards a more autonomous model based on the use of low carbon technologies, from the viewpoint of isolated communities in the industrialised world. The study begins by establishing the importance of isolated communities within the field of energy research, and examining the concept of low carbon energy autonomy. It then analyses a number of exemplary case studies from across Europe, all of which have adopted (or are in the process of adopting) a highly autonomous energy supply model based on the use of low carbon technologies. The communities studied exhibit many of the theoretical challenges and opportunities associated with low carbon energy autonomy, including the potential for stimulating socio-economic development. They also highlight the need for a supportive and structured policy framework and more transparent routes to project funding, in order to lessen the reliance for the success of such projects upon motivated community groups. The role of academia and its relationship with industry was found to be important and the findings call for much greater transparency and knowledge sharing between key stakeholders to facilitate increased development and deployment of low carbon energy autonomy in the future.